Kajian Pola Aliran dalam Reaktor Biodiesel dengan 4 Tipe Agitator melalui Simulasi Computational Fluid Dynamics - Sahrun Dongoran; Dyah Wulandani; Desrial Desrial (Jurnal Keteknikan Pertanian, 2022)
Biodiesel is formed by transesterification reaction of vegetable or animal fatty acid with alcohol. Agitation of fluid in the biodiesel reactor is required for occurring of the transesterification reaction. This research aims to study the flow behaviour in reactor with different type of agitator using computational fluid dynamics simulation and determine the optimum type of agitator in biodiesel production. Flow behaviour which was studied includes temperature and fraction distribution, turbulence intensity, and vorticity of fluid. The study was conducted in transient and steady state simulation with agitation types of helical screw, turbine, propeller, and anchor. The material that was modelled consist of cooking oil and methanol with mole ratio of 1:6. The mixing process used 500 rpm agitation speed and 60-65 oC mixing temperature. Furthermore, to determine the optimum agitator, the analytical hierarchy process method was carried out. The simulation results were analysed then obtained the score of each agitator, which were 0.314 (anchor), 0.350 (helical screw), 0.249 (propeller) and 0.087 (turbine). Based on the result, the optimum agitator was the helical screw type.